Sericea lespedeza (Lespedeza cuneata): seed dispersal, monitoring, and effect on species richness - Blocksome, Carolyn E. (Kansas State University, 2006)
Sericea lespedeza [Lespedeza cuneata (Dumont) G. Don] is a rangeland weed of the tallgrass prairie of Kansas. Experiments were carried out during the 2001-2003 growing seasons (June-November) to examine the relationship between sericea lespedeza and other rangeland species, wildlife use and dispersal of sericea lespedeza propagules, and the relationship between sericea lespedeza stubble height and utilization by livestock. Sericea lespedeza cover was positively correlated with violet lespedeza (r=0.25) [Lespedeza violacea (L.) Pers.], heath aster (Aster ericoides L.) (r=0.23) and total forb cover (r=0.56). Sericea lespedeza composition was negatively correlated with big bluestem (Andropogon gerardii Vitman.) (r=-0.27) and sideoats grama [Bouteloua curtipendula (Michx. Torr.)] (r=-0.27) composition and positively correlated with western ragweed (Ambrosia psilostachya D.C.) (r=0.21) and violet lespedeza (r=0.36) composition. Sericea lespedeza density was inversely related to forb species richness on all sites. On half the sites, there was also an inverse relationship between grass species richness and sericea lespedeza density. Grazed sites had less difference in grass species richness between high and low levels of sericea lespedeza densities. There was no evidence of an ecological threshold to the detriment of species richness with increasing sericea lespedeza density. Cattle digestive processes did not affect sericea lespedeza germination. Quail digestive processes enhanced germination of the few seeds that were excreted. Quail diet selection was investigated with a field study. Five out of 49 crops collected contained seed classified as sericea lespedeza. None of these seeds germinated in the greenhouse. Both cattle and quail could potentially disperse sericea lespedeza seed, but voluntary consumption appears to be low for both species, at least during November when other food is available. An height-weight table estimating percent utilization for various grazed and ungrazed heights of sericea lespedeza was constructed. Coefficient of determination values were greater than 0.85 between plant height and weight, indicating that the heightweight method was appropriate for estimating sericea lespedeza utilization. Using additional regression analysis, a chart for estimating forage from percent of plants grazed was constructed.
Keywords: range management; weed; bobwhite quail; range ecology; sericea lespedeza Lespedeza cuneata; Agriculture, Agronomy (0285); Agriculture, Range Management (0777); Biology, Ecology (0329)